Otimização do consumo energético de um sistema automatizado de irrigação pressurizado utilizando controle Fuzzy - Mendonça, Kamilla Henrique (2020)
In the irrigated agriculture sector, in order to increase productivity and profitability, it is necessary to increase the efficiency in the use of water and electricity. With this, the use of operational processes that maximize productivity in the sector, reducing the consumption of water and electricity, is gaining more and more space. This thesis proposed the development of an intelligent control system based on Fuzzy Logic, to control the pressure and flow at the entrances to the plots of a collective pressurized irrigation system. The tests developed to validate the proposal were applied to an experimental bench that emulates an automated water distribution system (SADA), installed at the Laboratory of Energy and Hydraulic Efficiency in Sanitation at the Federal University of Paraíba (LENHS / UFPB). The pressure control was done by varying the frequency of the pump set, while the flow was controlled by varying the opening of the control valves upstream of the entrance of each of the plots. With the application of the proposed methodology, the pumping system registered a reduction of 27% in its frequency of the propulsion system, when compared to its nominal operation value. From the reduction of the gross irrigation blade, the system showed a reduction of up to 34% in water consumption. Finally, through the energy analysis performed, after the application of the controller, the system was able to reduce electricity consumption by up to 52%. The results found validate the use of the controller in different irrigation scenarios, showing that the network was able to control the design flows and pressures with different set points.